The three pillars of effective European Union competition policy - Fiona Scott Morton (Bruegel, 2024)
Competitiveness is a region's ability to achieve high productivity, attracting businesses, creating jobs and fostering innovation. It stems from efficiently using resources, is driven by competitive markets and is supported by three pillars: competition policy, procompetitive industrial policy and regulation. Competition enforcement keeps markets competitive by preventing harmful practices such as cartels, dominance abuse and anticompetitive mergers. While there is a push to relax European Union merger laws to promote European 'champions', this risks inefficiency and monopolisation. Instead, expanding the EU's market size while maintaining competition is essential, especially in digital sectors. Procompetitive industrial policy addresses market failures and fosters well-functioning markets by targeting externalities such as worker training, R&D and infrastructure. Unlike outdated policies favouring national champions, this approach should focus on EU-level initiatives that promote competition and deepen the single market. This allows firms to achieve scale and drive innovation. Monopolised markets, whether state-created or naturally formed, need regulation to ensure competitive outcomes. The EU Digital Markets Act (DMA) aims to enhance competition and innovation on digital platforms by mandating data sharing, non-discriminatory access and interoperability. However, resistance to compliance on the part of tech giants poses enforcement challenges. Without effective and timely enforcement, trust in the law will erode, stalling innovation and reducing Europe's global regulatory influence. When competition enforcement, procompetitive industrial policy and monopoly regulation work together, markets benefit consumers, firms and workers. Effective EU policy will refine competition enforcement, regulate monopolies where necessary and redesign state aid strategically to create welfare-enhancing markets. This comprehensive approach ensures an economy that serves its people and remains competitive.
Keywords: 330; competition policy